Pyrophosphate-Bridged Cu II Chain Magnet: {[Na 3 Cu(P 2 O 7 )(NO 3 )]·3H 2 O} n - Sartoris, Rosana Patricia (2010)
A Cu(II)...Cu(II) pyrophosphate-bridged compound of formula {[Na(3)Cu(P(2)O(7))(NO(3))].3H(2)O}(n) (1) has been characterized. X-ray diffraction measurements show that it crystallizes in the monoclinic space group P2(1)/m, with unit cell dimensions a = 7.2492(5) A, b = 8.2446(6) A, c = 9.9050(7) A, beta = 107.123(1) degrees, and Z = 2. The structure consists of chains of Cu(II) cations at inversion symmetry sites bound to four equatorial oxygen atoms provided by two pyrophosphate anions halved by a symmetry plane and two axial oxygen atoms of nitrate anions. The molar magnetic susceptibility chi(0) of a powdered sample was measured in the temperature range 2 K < T < 273 K, and an isothermal magnetization curve, M(B(0),T), was obtained at T = 30 K, with the magnetic field B(0) between 0 and 5 T. Fitting a spin-chain model to the susceptibility data, we evaluate an antiferromagnetic exchange coupling 2J = -24.3(1) cm(-1) (defined as H(ex) = -2JS(i)S(j)) between Cu(II) neighbors. For any orientation of B(0), single-crystal electron paramagnetic resonance (EPR) spectra obtained at 9.8 and 33.9 GHz at 300 K display a single signal having a g matrix with orthorhombic symmetry, arising from the merger produced by the exchange interaction of the resonances corresponding to the two rotated Cu(II) sites. The g matrices of the individual molecules calculated assuming axial symmetry yielded principal values g(parallel) = 2.367(1) and g(perpendicular) = 2.074(1) at both frequencies, indicating a d(x(2)-y(2)) ground-state orbital for the Cu(II) ions. The angular variation of the EPR line width suggests exchange narrowing in a system with one-dimensional spin dynamics, as expected from the structure and susceptibility data. The results, discussed in terms of the crystal and electronic structures and of the spin dynamics of the compound, are compared with those obtained in other materials.